Strategi Dinas Pekerjaan Umum Dan Penataan Ruang Dalam Perbaikan Infrastruktur Jalan Di Kabupaten Bone - Fatimah, Sitti; Adys, Abdul Kadir; Rahim, Samsir (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This study purposed to find out the strategy of the Public Works and Spatial Planning Office in improving road infrastructure in Bone Regency. This study used descriptive research type with qualitative research type. This research data was collected through observation, interviews and documentation. The technique of validating the data was done by triangulating the source, technique and time and analyzed through data reduction, data presentation and verification. The results showed that the strategy of the Public Works and Spatial Planning Office in improving infrastructure in Bone Regency was not yet effective. Based on several strategic indicators in this study, namely: 1) Human resources, work results or work quality was low quality because the results of road repairs did not last long and were not  professional yet at work, 2) Effective, the work was still less effective due to limited funds which results in poor workmanship and damage quickly, 3) Efficient, not yet efficient because in road infrastructure improvements there were still some areas that had not been touched and evaluated for road infrastructure improvements, 4) Objectives, to improve the community's economy and the welfare of the people of Bone Regency.Keywords: Strategy, Repair, Road Infrastructure